Land, family and inheritance in Argentina's Pampas. Continuities and changes in the reproduction of capital (19th and 20th centuries) (Quinto Sol, 2013)
Our purpose in this essay is  to summarize the main conclusions we have arrived to in the last years, about inheritance, patrimony and family in the Argentinian pampas. Ruptures and continuities produced in patrimony transmission practices and in familiar reproduction modes developed in Argentinian pampas between the ninenteenth and twentieth centuries will be analyzed. This analysis is carried out giving priority to aspects such as: the normative context, the relationship between norm and practice, the coexistence of different juridical cultures, the land and changes concerning its meanings, the patrimony and the market, and the role of local institutions in familiar reproduction.
Keywords: Family; patrimony; inheritance; judicial institutions